Analysis of Eight Grade Students Failure in Solving Mathematical Problems - Minarni, Ani; Napitupulu, E. Elvis (Advances in Social Sciences Research Journal, 2018)
This research aimed to investigate the ability of eighth-grade students and types of error they made in solving mathematical problems. To obtain data, as many as 102 PJHS students are included in mathematical problem solving (MPS) test. The aspects of MPS ability used in this research consisted understanding the problem, proposed and used the strategy to solve the problem and conclude the solution in accordance to the initial problem. Results of the research: First, students MPS ability belong to the low category. The second one, types of error the students made in solving MPS consisted lack of algebra knowledge including algebra manipulation, lack of mathematical concept, and lack of informal and formal strategy including creating a picture. The third one, results of the interview reveal that the students view algebra as complicated material and does not have a definite pattern to conquer. Meanwhile, the students could not make a picture because they confuse in understanding words problems. Keywords: mathematical problem solving